2011
DOI: 10.1136/bjsm.2010.081554.5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resveratrol on the inflammatory response and delayed onset muscle soreness after a marathon in male athletes: a randomised, double-blind, placebo-controlled pilot study

Abstract: ObjectivesResveratrol, a natural polyphenolic flavonoid antioxidant is known to have numerous health benefits and to act as a potent anti-inflammatory substance. This study was undertaken to investigate the inflammatory responses and delayed onset of muscle soreness after the London Marathon, and whether it is altered by Resveratrol.Design and settingDouble placebo-controlled randomised trial conducted at the London Marathon, 2010.MethodsSeven healthy male athletes were recruited for the study. Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…A marathon race can evoke a profound systemic inflammatory response, evidence for which is provided by a number of studies that observed large systemic increases in cytokine and leucocyte activity (Suzuki et al 2003;Howatson et al 2010;Scherr et al 2011;Laupheimer et al 2014). Thus, it would be reasonable to assume that an intervention targeting the acute inflammatory response might help to minimize secondary muscle damage, which, in turn, might accelerate the recovery process after a marathon race.…”
Section: Introductionmentioning
confidence: 99%
“…A marathon race can evoke a profound systemic inflammatory response, evidence for which is provided by a number of studies that observed large systemic increases in cytokine and leucocyte activity (Suzuki et al 2003;Howatson et al 2010;Scherr et al 2011;Laupheimer et al 2014). Thus, it would be reasonable to assume that an intervention targeting the acute inflammatory response might help to minimize secondary muscle damage, which, in turn, might accelerate the recovery process after a marathon race.…”
Section: Introductionmentioning
confidence: 99%
“…All 50 studies were randomised controlled trials; no quasirandomised controlled trials met the inclusion criteria. Thirty-eight trials (with a total of 901 participants) employed a parallel design 21 22 27–60. The other 12 trials (with a total of 188 participants) employed a crossover design 61–72…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials were designed to produce DOMS under field-based conditions,22 35 44–46 64 and the other 43 studies were designed to produce DOMS under laboratory-based conditions. In all trials, an antioxidant supplement was compared with a placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Эти данные могут объяснять отсутствие влияния ресвератрола на сигнальную трансдукцию по NF-kB пути в отдельных исследованиях с участием здоровых лиц, но и определяют профиль его безопасности [23].…”
Section: Discussionunclassified